The effect of patient and prosthesis factors on revision rates after total knee replacement using a multi-registry meta-analytic approach - Lewis, Peter L; W-Dahl, Annette; Robertsson, Otto; Lorimer, Michelle; Prentice, Heather A; Graves, Stephen E; Paxton, Elizabeth W (Acta Orthopaedica, 2022)
Background and purpose: Characteristics of patients receiving total knee arthroplasty (TKA) and prostheses used vary between regions and change with time. How these practice variations influence revision remains unclear. We combined registry data for better understanding of the impact of variation, which could potentially improve revision rates. Patients and methods: We used data from 2003 to 2019 for primary TKA from arthroplasty registries of Sweden (SKAR), Australia (AOANJRR), and Kaiser Permanente (KPJRR). We included 1,072,924 TKA procedures for osteoarthritis. Factors studied included age, sex, ASA class, BMI category, prosthesis constraint, fixation, bearing mobility, patellar resurfacing, and polyethylene type. Cumulative percentage revision (CPR) was calculated using Kaplan–Meier estimates, and unadjusted Cox hazard ratios were used for comparisons. Random-effects generic inverse-variance meta-analytic methods were used to determine summary effects. Results: We found similarities in age and sex, but between-registry differences occurred in the other 7 factors studied. Patients from Sweden had lower BMI and ASA scores compared with other registries. Use of cement fixation was similar in the SKAR and KPJRR, but there were marked differences in patellar resurfacing and posterior stabilized component use. Meta-analysis results regarding survivorship favored patients aged ≥ 65 years and minimally stabilized components. There were inconsistent results with time for sex, fixation, and bearing mobility, and no differences for the patellar resurfacing or polyethylene type comparisons. Interpretation: Marked practice variation was found. Use of minimally stabilized and possibly also cemented and fixed bearing prostheses is supported.